Modeling and control of a nonholonomic wheeled mobile robot with wheel slip dynamics - Tian, Yu; Sidek, Shahrul Na'im; Sarkar, Nilanjan (2009)
In order to model a Wheeled Mobile Robot(WMR) system to improve its maneuverability in a real environment, wheel dynamics, which may violate no-slipping and pure rolling constraints, needs to be studied. In this paper,wheel dynamics with slip is modeled and introduced into the robot overall dynamics. Wheel slip phenomenon is captured and at the same time accommodated. Considering both lateral and longitudinal slip phenomena due to traction, a WMR system becomes an underactuated dynamic system. A time-invariant discontinuous feedback law is developed to asymptotically stabilize the system to the desired configuration with exponential convergence rate. Simulation results are provided to validate the theoretical results.